Implicit and explicit prosocial motivation as antecedents of volunteering: The moderating role of parenthood. (February 2015) - Aydinli, Arzu; Bender, Michael; Chasiotis, Athanasios; van de Vijver, Fons J.R.; Cemalcilar, Zeynep
Highlights: We examine motives to volunteer for parents and non-parents from Turkey and the US. We found parents' volunteering to be related to implicit prosocial motivation. We found non-parents' volunteering to be related to explicit prosocial motivation. Relationships were invariant across the two cultural groups. Abstract: We test a model proposing that having children influences motivational pathways of volunteering in the same way across two different cultures. The model posits that parents' engagement in volunteering is driven by implicit, whereas non-parents' engagement in volunteering is related to explicit prosocial motivation. Participants were 570 parents and non-parents from Turkey and the US ( Mage  = 33.7 years; 58.2% female). Results across the two cultural contexts confirmed our model. Our findings highlight the need for considering implicit prosocial motivation as an antecedent of volunteering, and underline the importance of examining parenthood as a moderator for motivations to volunteer. Avenues for further research and implications for voluntary organizations are discussed.